Self-crosslinking multi-component graft copolymerization paper reinforcing agent and preparation method thereof

Through the preparation method of multi -component branches and closure polymerization agents, the existing paper enhancers are complex, high cost, unstable performance, and environmental impact, and realize the significance of paper strength and water resistance performance. Improvement meets the requirements of environmental protection and sustainable development.

CN119331173AActive Publication Date: 2025-01-21SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411728706.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-21
Estimated Expiration
2044-11-28

Smart Images

  • Figure CN119331173A_ABST
    Figure CN119331173A_ABST
Patent Text Reader

Abstract

The invention discloses a self-crosslinking type multi-component graft copolymerization paper reinforcing agent and a preparation method, and belongs to the technical field of papermaking. Carboxymethyl cellulose is used as a dispersing agent, isopropanol is used as a chain transfer agent, deionized water is used as a solvent, and the self-crosslinking type multi-component graft copolymerization paper reinforcing agent is prepared. The preparation method comprises the following steps: initiating polymerization reaction of methacryloyloxyethyl trimethyl ammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid at 50-80 DEG C under the action of an initiator; the mass ratio of the carboxymethyl cellulose to the methacryloyloxyethyl trimethyl ammonium chloride to the acrylamide to the acrylic acid to the 2-acrylamide-2-methylpropanesulfonic acid is (1-10): (1-5): (10-30): (1-10): (1-5), and then adjusting the pH value of the obtained reaction solution to 4.5-5.5 to obtain the self-crosslinking type multi-component graft copolymerization paper reinforcing agent. The stability of a cross-linked structure of the reinforcing agent is improved, the binding power is increased, and the strength and the water resistance of paper can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of papermaking, and in particular relates to a self-crosslinking multi-component graft copolymer paper reinforcing agent and a preparation method thereof. Background Art

[0002] With the rapid development of the papermaking industry, the requirements for paper quality and performance are constantly increasing, so paper enhancement technology is needed. Paper enhancement technology is to improve the physical properties, chemical properties and printability of paper through a series of processes and methods to meet the high requirements of paper quality in different fields. Paper enhancer is a chemical additive specially used to improve the physical properties of paper. It usually exists in the form of liquid coating and is composed of a variety of chemicals. It has the characteristics of enhancing paper toughness, water resistance, and anti-aging. In the papermaking process, adding paper enhancer to pulp or coating it on the surface of paper can significantly improve the performance indicators of paper such as tensile strength, tear resistance, folding resistance and burst resistance. Therefore, as a key auxiliary agent to improve the physical properties of paper, the research and development and application of paper enhancer have received widespread attention.

[0003] In the existing paper enhancement technology, commonly used enhancers have various limitations. For example, the effect of a single-component enhancer is relatively limited, and it is difficult to comprehensively improve the various performance indicators of paper. Some enhancers only have a certain improvement on a specific property of paper, but have a weak effect on improving other important properties. Some enhancers have a complicated and cumbersome preparation process and high cost, which is not conducive to large-scale production and wide application. In addition, some traditional enhancers will also have adverse effects on the environment, which is inconsistent with the current green environmental protection concept.

[0004] In recent years, polymer paper enhancers have attracted much attention due to their unique properties. However, existing polymer enhancers often have problems such as complex process, high cost and unstable performance during preparation. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a self-crosslinking multi-component graft copolymer paper strengthening agent and a preparation method thereof. The preparation process is simple, the cost is low and the environment is friendly. The monomers of each component are copolymerized and grafted with carboxymethyl cellulose to form a crosslinked network structure, which increases the stability of the crosslinked structure, enhances the bonding force, and can significantly improve the strength and water resistance of paper.

[0006] The present invention is achieved through the following technical solutions: A method for preparing a self-crosslinking multi-component graft copolymer paper reinforcing agent comprises the following steps: using carboxymethyl cellulose as a dispersant, isopropanol as a chain transfer agent and deionized water as a solvent, initiating a polymerization reaction of methacryloyloxyethyl trimethyl ammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methyl propane sulfonic acid at 50-80° C. under the action of an initiator, wherein the mass ratio of carboxymethyl cellulose, methacryloyloxyethyl trimethyl ammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methyl propane sulfonic acid is (1-10): (1-5): (10-30): (1-10): (1-5), and then adjusting the pH of the obtained reaction solution to 4.5-5.5 to obtain a self-crosslinking multi-component graft copolymer paper reinforcing agent.

[0007] A further improvement of the present invention is: The specific steps include: S1, dissolving carboxymethyl cellulose in deionized water, then adding isopropanol and stirring to obtain a first mixed solution; S2, dissolving methacryloyloxyethyltrimethylammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid in deionized water to obtain a second mixed solution; dissolving the initiator in deionized water to obtain an aqueous solution; S3, adding the second mixed solution and the aqueous solution to the first mixed solution at 50-80° C. simultaneously and at a uniform rate, then keeping the mixture at 50-80° C., and adjusting the pH of the obtained reaction solution to 4.5-5.5 to obtain a self-crosslinking multi-component graft copolymer paper strengthening agent.

[0008] The carboxymethyl cellulose described in S1 is 1%-5% of the total mass of methacryloyloxyethyltrimethylammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid.

[0009] The initiator described in S2 is ammonium persulfate or potassium persulfate.

[0010] The ammonium persulfate or potassium persulfate is 0.1%-3% of the total mass of methacryloyloxyethyltrimethylammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid.

[0011] S1 In the first mixed solution, the mass ratio of carboxymethyl cellulose to deionized water is (1-5):100.

[0012] S2 In the second mixed solution, the mass ratio of acrylamide to deionized water is (1-3): (1-5), and in the aqueous solution, the mass ratio of initiator to deionized water is (0.1-1): (1-20).

[0013] The time for adding the second mixed solution and the aqueous solution in S3 is 1-3 hours.

[0014] The insulation time in S3 is 1-3h.

[0015] A self-crosslinking multi-component graft copolymer paper strengthening agent obtained by the preparation method of the self-crosslinking multi-component graft copolymer paper strengthening agent described in any one of the above.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a self-crosslinking multi-component graft copolymer paper reinforcing agent. CMC has good dispersibility and water solubility, making the reaction system more stable, and helping to ensure the consistency and reliability of the quality of the reinforcing agent. The performance fluctuation caused by unstable reaction is reduced, and the controllability of the preparation process is improved. Isopropyl alcohol is used as a chain transfer agent, and an initiator is used to initiate the polymerization reaction. The monomers methacryloyloxyethyl trimethyl ammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropane sulfonic acid are copolymerized and grafted with carboxymethyl cellulose at the same time. The initiator will decompose and generate free radicals under the condition of 50-80°C. These free radicals will attack the above monomers containing carbon-carbon double bonds. Taking AM as an example, the free radicals attack the double bonds of AM, open the double bonds, and form an active monomer free radical (·CH-CH(CONH2)). The formed monomer free radical has a high reactivity and will quickly continue to react with the double bonds of other monomer molecules. In a system with multiple monomers, they will compete with each other to participate in chain growth. The growing polymer chain will react with the carboxymethyl cellulose (CMC) main chain. There are many active groups on the CMC main chain, such as hydroxyl (-OH). When the polymer chain free radical approaches the CMC main chain, it will capture the hydrogen atom on the CMC hydroxyl to form a water molecule. At the same time, the polymer chain free radical is connected to the CMC main chain by forming a new chemical bond. When the growing polymer chain free radical comes from AMPS , after encountering the hydroxyl group on the CMC main chain, the reaction formula is: ·CH2-CH(CONHCH2C(CH3)2SO3H)+CMC-OH, and the reaction forms: CMC-O-CH2-CH(CONHCH2C(CH3)2SO3H), which realizes the grafting of the AMPS segment on the CMC main chain, thereby forming a cross-linked network structure, increasing the stability of the cross-linked structure, and increasing the bonding force. The prepared paper enhancer has excellent performance, moderate cost, environmental protection and easy operation, good enhancement effect, stable performance, convenient use, low cost, and can significantly improve the strength and water resistance of paper. It can be used to produce high-quality packaging paper, printing paper, specialty paper, etc., to meet the high requirements of paper quality in different application scenarios, and can better meet the needs of the continuous development of the papermaking industry. Compared with a single-component enhancer, the enhancer prepared by the present invention improves the performance of paper more comprehensively and significantly. The raw materials used in the preparation process of the present invention are relatively environmentally friendly, and fewer pollutants are generated during the reaction process. Compared with some traditional enhancers, it has less impact on the environment, which is in line with the current development concept of green environmental protection. By improving the strength and durability of paper, the amount of paper used can be reduced, thereby saving natural resources such as wood and meeting the requirements of sustainable development.

[0017] Furthermore, isopropanol was used as a chain transfer agent and ammonium persulfate was used as an initiator. Ammonium persulfate produced sulfate radicals (SO4 -·), the reaction conditions are mild and easy to control, avoiding the equipment requirements and safety risks of harsh reaction conditions such as high temperature and high pressure, reducing production costs and production difficulties, and facilitating large-scale production and promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the infrared spectrum of the self-crosslinking multi-component graft copolymer paper strengthening agent of the present invention.

[0019] Figure 2 This is a stability test chart of the self-crosslinking multi-component graft copolymer paper strengthening agent of the present invention.

[0020] Figure 3 This is the effect of the AMPS content on the dry tensile index and wet tensile index of paper according to the present invention.

[0021] Figure 4 This is the effect of the AMPS content on the folding strength and tearing strength of paper according to the present invention. DETAILED DESCRIPTION

[0022] The present invention is described in detail below in conjunction with embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.

[0023] The invention discloses a self-crosslinking multi-component graft copolymer paper strengthening agent. The raw materials include dispersant CMC (carboxymethyl cellulose), chain transfer agent isopropyl alcohol, initiator persulfate (ammonium persulfate or potassium persulfate), comonomer DMC (methacryloyloxyethyl trimethyl ammonium chloride), AM (acrylamide), AA (acrylic acid) and AMPS (2-acrylamide-2-methylpropane sulfonic acid), wherein the mass ratio of CMC, DMC, AM, AA and AMPS is (1-10): (1-5): (10-30): (1-10): (1-5), the isopropyl alcohol accounts for 1%-5% of the total mass of CMC, DMC, AM, AA and AMPS, and the added amount of the initiator accounts for 0.1%-3% of the total mass of CMC, DMC, AM, AA and AMPS.

[0024] The present invention discloses a method for preparing a self-crosslinking multi-component graft copolymer paper strengthening agent, comprising the following steps: Step 1: Dissolution of CMC At 60-80°C, CMC is dissolved in deionized water to prepare a solution with a mass percentage of 1-5%, and then isopropanol is added and stirred for 2-10 minutes to obtain a transparent viscous mixed solution.

[0025] Step 2: Preparation of enhancer (1) Dissolve AM, AA, AMPS, and DMC in deionized water and stir evenly to prepare a mixed solution, in which the mass ratio of AM to deionized water is (1-3): (1-5).

[0026] (2) Dissolve the initiator in deionized water to prepare an initiator aqueous solution, wherein the mass ratio of the initiator to the deionized water is (0.1-1):(1-20).

[0027] (3) Slowly drop the solution prepared in step (1) and step (2) into the mixed solution of CMC and isopropanol at 50-80°C, and control the dropping time to be 60-180 min. After the dropping is completed, keep the temperature at this temperature for 1-3 h, then cool to room temperature, and adjust the pH to 4.5-5.5 with 25-28% by mass of ammonia water to obtain a cross-linked multi-component graft copolymer paper strengthening agent sol, which is used to improve the strength properties of paper, including tensile index, folding strength, tear strength and bursting strength.

[0028] Example 1 2 g of CMC was dissolved in deionized water at 60°C to prepare a 5% solution by mass, and then 0.5 g of isopropanol was added and stirred for 10 min to obtain a transparent viscous mixed solution.

[0029] The mixed solution of CMC and isopropanol was heated to 80°C, 10g AM, 3g AA, 0.5g AMPS, and 2g DMC were dissolved in 50g deionized water and stirred evenly to prepare an aqueous solution; Dissolve 0.2 g of ammonium persulfate in 10 g of deionized water to prepare an aqueous solution; The above two aqueous solutions were added dropwise to the mixed solution of CMC and isopropanol through a constant pressure funnel respectively, ensuring that the dropping was completed at the same time. The dropping time was controlled within 60 minutes. After the dropping was completed, the solution was kept warm for 2 hours and then cooled to room temperature. The pH was adjusted to 5 with 26% by mass ammonia water to obtain a cross-linked multi-component graft copolymer paper reinforcing agent sol.

[0030] Example 2 2 g of CMC was dissolved in deionized water at 60°C to prepare a 5% solution by mass, and then 0.5 g of isopropanol was added and stirred for 10 min to obtain a transparent viscous mixed solution.

[0031] Heat the mixed solution of CMC and isopropanol to 80°C, dissolve 10g AM, 3g AA, 1g AMPS, and 2g DMC in 50g deionized water and stir evenly to prepare an aqueous solution; Dissolve 0.2 g of ammonium persulfate in 10 g of deionized water to prepare an aqueous solution; The above two aqueous solutions were added dropwise to the mixed solution of CMC and isopropanol through a constant pressure funnel respectively, ensuring that the solution was added simultaneously. The adding time was controlled within 60 min. After the addition was completed, the solution was kept warm for 2 h, then cooled to room temperature, and the pH was adjusted to 5 with 26% by mass ammonia water to obtain a cross-linked multi-component graft copolymer paper reinforcing agent sol.

[0032] Example 3 2 g of CMC was dissolved in deionized water at 60°C to prepare a 5% solution by mass, and then 0.5 g of isopropanol was added and stirred for 10 min to obtain a transparent viscous mixed solution.

[0033] The mixed solution of CMC and isopropanol was heated to 80°C, 10g AM, 3g AA, 1.5g AMPS, and 2g DMC were dissolved in 50g deionized water and stirred evenly to prepare an aqueous solution; Dissolve 0.2 g of ammonium persulfate in 10 g of deionized water to prepare an aqueous solution; The above two aqueous solutions were added dropwise to the mixed solution of CMC and isopropanol through a constant pressure funnel respectively, ensuring that the solution was added simultaneously. The adding time was controlled within 60 min. After the addition was completed, the solution was kept warm for 2 h, then cooled to room temperature, and the pH was adjusted to 5 with 26% by mass ammonia water to obtain a cross-linked multi-component graft copolymer paper reinforcing agent sol.

[0034] Example 4 2 g of CMC was dissolved in deionized water at 60°C to prepare a 5% solution by mass, and then 0.5 g of isopropanol was added and stirred for 10 min to obtain a transparent viscous mixed solution.

[0035] Heat the mixed solution of CMC and isopropanol to 80°C, dissolve 10g AM, 3g AA, 2.5g AMPS and 2g DMC in 50g deionized water and stir evenly to prepare an aqueous solution; Dissolve 0.2 g of ammonium persulfate in 10 g of deionized water to prepare an aqueous solution; The above two aqueous solutions were added dropwise to the mixed solution of CMC and isopropanol through a constant pressure funnel at the same time to ensure that they were added at the same time. The adding time was controlled within 60 minutes. After the addition was completed, the temperature was kept for 2 hours and then cooled to room temperature. The pH was adjusted to 5 with 28% by mass ammonia water to obtain a cross-linked multi-component graft copolymer paper reinforcing agent sol.

[0036] Comparative Example 1 2 g of CMC was dissolved in deionized water at 60°C to prepare a 5% solution by mass, and then 0.5 g of isopropanol was added and stirred for 10 min to obtain a transparent viscous mixed solution.

[0037] Heat the mixed solution of CMC and isopropanol to 80°C, dissolve 10g AM, 3g AA, and 2g DMC in 50g deionized water and stir evenly to prepare an aqueous solution; Dissolve 0.2 g of ammonium persulfate in 10 g of deionized water to prepare an aqueous solution; The two aqueous solutions were added dropwise to the mixed solution of CMC and isopropanol through a constant pressure funnel at the same time to ensure that they were added at the same time. The adding time was controlled within 60 minutes. After the addition was completed, the solution was kept warm for 2 hours and then cooled to room temperature. The pH was adjusted to 5 with 26% by mass ammonia water to obtain a paper strengthening agent sol.

[0038] Analysis of the structure and properties of synthetic paper strengthening agents FT-IR Analysis of Self-crosslinking Multi-component Graft Copolymer Paper Strengthening Agent Figure 1 In the spectrum, the broad strong absorption peak at 3308cm-1 is the stretching vibration absorption peak of hydroxyl group (—OH); the weak absorption peak at 2113cm-1 is the stretching vibration absorption peak of sulfur oxygen double bond (S=O), the stronger absorption peak at 1641cm-1 is the stretching vibration peak of amide carbonyl group (C=O), 1563cm-1 is the symmetric stretching vibration peak of COO-, indicating that CMC and monomer are successfully grafted, the absorption peak at 1456cm-1 is the bending vibration absorption peak of N+(CH3)3, and 1041cm-1 is the CO vibration absorption peak. No characteristic absorption peak of carbon-carbon double bond (C=C) is found in the polymer in the spectrum. The monomer reaction is complete in the reaction, which is consistent with the structural characteristics of self-crosslinking multi-component graft copolymer paper enhancer.

[0039] Stability analysis of self-crosslinking multi-component graft copolymer paper strengthening agent Depend on Figure 2It can be seen that in the 60-min test, the TSI values ​​of all sol samples showed an increasing trend. TSI is an indicator for evaluating the stability of liquid dispersion systems. Within a fixed aging time, the smaller the TSI index, the more stable the sol. When the AMPS addition reaches 8.1%, the TSI value of the sol is the smallest and the stability of the sol is the best. This is because AMPS has a strong anionic sulfonate group, which can prevent the polymer chains from entangled and agglomerated through charge repulsion. When the AMPS addition is 2.85%, due to the small number of sulfonate groups and weak charge repulsion, there is a certain degree of entanglement between the polymer chains. Over time, the sol will show a slight flocculation phenomenon, resulting in a decrease in the stability of the sol. When the AMPS addition reaches 8.1%, there are enough sulfonate groups to effectively support the polymer chains, so that the polymer chains can be evenly dispersed in the aqueous solution, making the sol stable. When excessive AMPS is added, too much AMPS will cause the charge density on the polymer chain to be too high, triggering excessive electrostatic repulsion and making the polymer chain too loose. In addition, AMPS itself has a certain spatial structure, and the increase in the amount added will produce steric hindrance. This effect hinders the movement and reaction of other molecules in the system, resulting in reduced stability of the system.

[0040] Performance testing experiment The self-crosslinking multi-component graft copolymer paper strengthening agent prepared as above was sheeted as follows: 2 Weigh a certain mass of bleached refined cotton pulp, add 0.6% (mass ratio of absolute dry pulp) of self-crosslinking multi-component graft copolymer paper reinforcing agent and 1.6% (mass ratio of absolute dry pulp) of PAE in turn, and decompose in a standard fiber decompressor, rotating 6000 times per minute, so that the self-crosslinking multi-component graft copolymer paper reinforcing agent is adsorbed on the fiber through hydrogen bonding and electrostatic action, and then use a paper sample copying machine to copy a quantitative 95g / m 2 The paper was then vacuum dried at 105°C for 10 min and the physical properties of the finished paper were tested.

[0041] The physical properties of paper are tested and calculated in accordance with national standards. The tensile index refers to GB / T 12914-2008 Determination of tensile strength of paper and paperboard; the tear strength refers to GB / T 455-2002 Determination of tear resistance of paper and paperboard; the folding strength refers to GB / T 457-2008 Determination of folding endurance of paper and paperboard.

[0042] Effect of AMPS content on paper strength properties In order to determine the optimal content of AMPS, the strength properties of paper were tested when the self-crosslinking multi-component graft copolymer paper strengthening agent was added at 0.6%. The results are as follows Figure 3 and Figure 4 When the content of AMPS is 0%, the dry tensile index of the sized paper is 65.5N·m / g, the wet tensile index is 15.1N·m / g, the folding strength is 130 times, and the tear strength is 13.4N·m2 / g. Figure 3 and Figure 4 It can be seen that the dry and wet tensile indexes of the sized paper first show an upward trend with the increase of AMPS content. This is because the positive charge carried by the self-crosslinking multi-component graft copolymer paper reinforcing agent itself attracts the negative charge on the cotton pulp fiber, adsorbing the self-crosslinking multi-component graft copolymer paper reinforcing agent on the fiber surface. In addition, the amino, carbonyl, and carboxyl functional groups on the polymer chain segments will also react with the hydroxyl groups on the cotton pulp fiber to form a cross-linked structure, thereby increasing the toughness and strength between the fibers. When the AMPS content is 8.1%, the dry tensile index of the paper reaches 68.4N·m / g, the wet tensile index reaches 18.8N·m / g, the folding strength reaches 121 times, and the tear strength reaches 14.2N·m 2 / g, compared with the paper without internal sizing, the paper strength indexes increased by 32%, 487.5%, 348% and 5.2% respectively. However, with the increasing content of AMPS, the dry and wet strength indexes of the paper decreased. This is because the self-aggregation of the polymer chain segments is too large, resulting in flocculation. In summary, the optimal amount of AMPS is 8.1%.

Claims

1. A method for preparing a self-crosslinking multi-component graft copolymer paper strengthening agent, characterized in that: With carboxymethyl cellulose as a dispersant, isopropanol as a chain transfer agent and deionized water as a solvent, methacryloyloxyethyl trimethyl ammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methyl propane sulfonic acid are reacted at 50-80° C. under the action of an initiator. The mass ratio of carboxymethyl cellulose, methacryloyloxyethyl trimethyl ammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methyl propane sulfonic acid is (1-10): (1-5): (10-30): (1-10): (1-5). Then, the pH of the obtained reaction solution is adjusted to 4.5-5.5 to obtain a self-crosslinking multi-component graft copolymer paper reinforcing agent.

2. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 1, characterized in that: The specific steps include: S1, dissolving carboxymethyl cellulose in deionized water, then adding isopropanol and stirring to obtain a first mixed solution; S2, dissolving methacryloyloxyethyltrimethylammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid in deionized water to obtain a second mixed solution; dissolving the initiator in deionized water to obtain an aqueous solution; S3, adding the second mixed solution and the aqueous solution to the first mixed solution at 50-80° C. simultaneously and at a uniform rate, then keeping the mixture at 50-80° C., and adjusting the pH of the obtained reaction solution to 4.5-5.5 to obtain a self-crosslinking multi-component graft copolymer paper strengthening agent.

3. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 2, characterized in that: The carboxymethyl cellulose described in S1 is 1%-5% of the total mass of methacryloyloxyethyltrimethylammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid.

4. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 2, characterized in that: The initiator described in S2 is ammonium persulfate or potassium persulfate.

5. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 4, characterized in that: The ammonium persulfate or potassium persulfate is 0.1%-3% of the total mass of methacryloyloxyethyltrimethylammonium chloride, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid.

6. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 2, characterized in that: S1 In the first mixed solution, the mass ratio of carboxymethyl cellulose to deionized water is (1-5):

100.

7. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 2, characterized in that: S2 In the second mixed solution, the mass ratio of acrylamide to deionized water is (1-3): (1-5), and in the aqueous solution, the mass ratio of initiator to deionized water is (0.1-1): (1-20).

8. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 2, characterized in that: The time for adding the second mixed solution and the aqueous solution in S3 is 1-3 hours.

9. The method for preparing the self-crosslinking multi-component graft copolymer paper strengthening agent according to claim 2, characterized in that: The insulation time in S3 is 1-3h.

10. A self-crosslinking multi-component graft copolymer paper strengthening agent obtained by the preparation method of the self-crosslinking multi-component graft copolymer paper strengthening agent according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Graft polymer

    CN101142243A

  • Cellulose graft copolymer, and preparation method and application thereof

    CN109970916A

  • Modified carboxymethyl cellulose for papermaking coating as well as preparation method and application of modified carboxymethyl cellulose

    CN116575260A

  • Preparation method and application of packaging paper super-effect enhancer

    CN118562057A

  • Paper strength improving additives, their manufacture and use in paper making

    US20210222368A1

Cited By

  • A fluorine-free environmentally friendly oil-proof agent for paper base and its preparation method and application

    CN119754087A